2004
DOI: 10.1158/0008-5472.can-03-2915
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Treatment with CPT-11 Leads to Differentiation of Neuroblastoma Xenografts and Topoisomerase I Alterations

Abstract: Topoisomerase I inhibitors, such as CPT-11, are potent anticancer drugs against neuroblastoma (NB). Differentiating agents, such as retinoids, improve the survival of children with metastatic NB. To characterize the biological effects associated with exposure to CPT-11 in vivo, athymic mice bearing a human NB xenograft, named IGR-NB8 and characterized as an immature NB with poor prognostic markers, were treated with CPT-11. Prolonged stable disease was observed, resulting in an overall tumor growth delay of 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The parental xenografts displayed the histological features of a poorly differentiated NB composed of undifferentiated neuroblastic cells (small uniform rounded cells) containing a high number of mitotic figures per high-power field and very little schwannian stroma ( Figure 4A). During the first two passages, the stabilisation state was associated with tumour differentiation exhibiting features of a maturing ganglioneuroma (Santos et al, 2004) However, the IGR-NB8-R-resistant xenografts showed similar histological features to those observed in the parental xenografts ( Figure 4A), namely those of a poorly differentiated NB ( Figure 4B). These results indicate that there was no modification of histological features during the acquisition of resistance.…”
Section: Characterisation Of Igr-nb8-rmentioning
confidence: 72%
See 1 more Smart Citation
“…The parental xenografts displayed the histological features of a poorly differentiated NB composed of undifferentiated neuroblastic cells (small uniform rounded cells) containing a high number of mitotic figures per high-power field and very little schwannian stroma ( Figure 4A). During the first two passages, the stabilisation state was associated with tumour differentiation exhibiting features of a maturing ganglioneuroma (Santos et al, 2004) However, the IGR-NB8-R-resistant xenografts showed similar histological features to those observed in the parental xenografts ( Figure 4A), namely those of a poorly differentiated NB ( Figure 4B). These results indicate that there was no modification of histological features during the acquisition of resistance.…”
Section: Characterisation Of Igr-nb8-rmentioning
confidence: 72%
“…Moreover Western blot analysis of topoisomerase I showed no difference between the tumours studied ( Figure 7). The human polyclonal anti-topoisomerase I antibody revealed two main bands located at 100 kDa, corresponding to a full-length enzyme and at 54 kDa, a form specific to human tissues (Santos et al, 2004) and perhaps the heavy chain of the immunoglobulin molecule (Bronstein et al, 1996). Thus, topoisomerase expression and activity was not implicated in the in vivo resistance acquisition.…”
Section: Analysis Of Topoisomerase Imentioning
confidence: 99%
“…Low concentration of HCPT and its analogs have been proven to have potent differentiation-inducing activity in several kinds of human cancer cells in vitro. Therefore, we chose HCPT as a differentiation-inducing agent and used the concentration of 0.02 lg/ml, as described in previous studies [15,16,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HCPT and its analogs have been proven to have potent differentiation-inducing activity in human cancer cells [14][15][16]. CSCs play important roles in the development and progression of malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…The active metabolite of CPT-11, SN-38, stabilizes a ternary complex between the nuclear enzyme topoisomerase I and double-stranded DNA [7]. As reported by Santos et al, CPT-11 shows marked antitumoral activity against pediatric xenografts in preclinical studies [8,9]. Topotecan is used as a standard treatment in ovarian cancer, and it was recently reported to be eVective in a small percentage of patients with relapsed or refractory neuroblastoma [10][11][12].…”
Section: Introductionmentioning
confidence: 99%